Sex-Specific Selection and the Evolution of Between-Sex Genetic Covariance. (29th June 2019) - McGlothlin, Joel W; Cox, Robert M; Brodie, Edmund D
Abstract: Because the sexes share a genome, traits expressed in males are usually genetically correlated with the same traits expressed in females. On short timescales, between-sex genetic correlations ( r mf ) for shared traits may constrain the evolution of sexual dimorphism by preventing males and females from responding independently to sex-specific selection. However, over longer timescales, r mf may evolve, thereby facilitating the evolution of dimorphism. Although it has been suggested that sexually antagonistic selection may reduce r mf, we lack a general theory for the evolution of r mf and its multivariate analog, the between-sex genetic covariance matrix (B ). Here, we derive a simple analytical model for the within-generation change in B due to sex-specific directional selection. We present a single-trait example demonstrating that sex-specific directional selection may either increase or decrease between-sex genetic covariance, depending on the relative strength of selection in each sex and on the current value of r mf . Although sexually antagonistic selection can reduce between-sex covariance, it will only do so when selection is much stronger in one sex than in the other. Counterintuitively, sexually antagonistic selection that is equal in strength in the 2 sexes will maintain positive between-sex covariance. Selection acting in the same direction on both sexes is predicted to reduce between-sex covariance in many cases. We illustrate our model numerically using empirical measures of sex-specific selection and between-sex genetic covariance from 2 populations of sexually dimorphic brown anole lizards ( Anolis sagrei ) and discuss its importance for understanding the resolution of intralocus sexual conflict.